Sensors in electronic applications - Tasnim, Rumana; Arshad, Atika; Khan, Sheroz; Ahmed, Musse Mohamud (IIUM Press, 2011)
In response to any change in the measuring quantity (stimulus), input type transducers or sensors generate a proportional output voltage or signal which basically depends on the sensor type in use. Usually sensors are categorized into two types: active and passive sensors. There are also some other type of sensors such as; digital sensors, deflection sensors and null sensors. In this chapter only active and passive sensors will be discussed in depth. Based on the sensors' working mechanism the classification of sensors can be done. Resistive sensors include temperature sensors, strain gauges, photoresistors, relative humidity sensors, position/angle sensors, GMR sensors etc. Several voltage generating sensors are quite in use that includes thermocouples and thermopiles, photovoltaic cells, piezoelectric transducers, pyroelectric sensors, magnetic field voltage generating sensors, hall sensors etc, which are quite recognizable. Other working mechanism offers a number of sensors like variable magnetic coupling sensors, variable capacitance sensors, fiber optic sensors, magneto-optic sensors, photomultipliers etc.